(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe some clinical and paraclinical characteristics and analyze changes in plasma CA 15-3 levels in breast cancer patients treated with Tamoxifen at K Hospital from 2019 to 2022. Research methods: Cross-sectional descriptive study was performed using secondary data on medical records of patients with a confirmed diagnosis of breast cancer, receiving endocrine treatment with Tamoxifen at K Hospital, from 2019 to September 2022 and continuous monitoring for at least 6 months. Results: Research results showed that breast cancer patients often have tumors in the most common location, 1/4 on the outside, accounting for 43.1%. Tumors may or may not cause pain, and most tumors have firm density (57.7%), unclear borders (60.2%). The ER receptor with positive status was 99.4%, PR receptor with positive status was 91.4%, and both receptors with positive status were 87.2%. CA 15-3 concentration after treatment was lower than that before treatment. CA 15-3 results at 3 time points dispersed around median values ​​of 16.59 U/mL (before treatment), 14.94 U/mL (3 months after treatment) and 14.42 U/mL (6 months after treatment), respectively. The proportion of patients with CA 15-3 levels within normal limits gradually increased over time of treatment (89.6% before treatment; 93.8% after 3 months of treatment; 95.8% after 6 months, p < 0.05). Conclusion: The cancer marker CA 15-3 combined with clinical and paraclinical characteristics after each treatment cycle plays an important role in supporting to evaluate the effectiveness of breast cancer treatment with Tamoxifen.